Effect of topical PTH 1-34 functionalized to biogran® in the process of alveolar repair in rats submitted to orchiectomy - Frigério, Paula Buzo [UNESP]; Gomes-Ferreira, Pedro Henrique Silva [UNESP]; de Souza Batista, Fábio Roberto [UNESP]; Moura, Juliana [UNESP]; Júnior, Idelmo Rangel Garcia [UNESP]; Botticelli, Daniele; Lisboa-Filho, Paulo Noronha [UNESP]; Okamoto, Roberta [UNESP] (MDPI, 2022)
(1) Background: There are many therapies for osteoporosis control and bone maintenance; anabolic drugs such as teriparatide and bone grafts help in the repair process and stimulate bone formation. Thus, the aim of the present study was to evaluate the behavior of repaired bone in the presence of PTH (teriparatide) associated with Biogran® (biomaterial) through a sonochemical procedure after extraction in rats. (2) Methods: The insertion of Biogran® with PTH in the alveolus was performed 30 days after incisor extraction. Euthanasia occurred after 60 days. (3) Results: The use of local treatment of PTH loaded with Biogran®in healthy rats promoted good results for micro-CT, with an increase in percentage and bone volume, number and trabecular separation and less total porosity. Greater immunostaining for Wnt, β-Catenin and osteocalcin proteins and lower expression for Thrombospondin-Related Adhesive Protein (TRAP), which shows an increase in the number of osteoblasts and inhibition of osteoclast action. However, the treated orchiectomized groups did not obtain such expressive results. (4) Conclusion: The use of Biogran® with PTH improved alveolar repair in rats. However, new researches with more efficient doses must be studied to collaborate effectively with the formation of a quality bone after the orchiectomy.
Keywords: Biomaterial; Bone regeneration; Men; Orchiectomy; Osteoporosis; Parathyroid hormone